Analisis Penilaian Kinerja Keuangan Perusahaan Dengan Menggunakan Metode Economic Value Added (EVA) (Studi Pada Perusahaan Yang Bergerak Di Bidang Otomotif Yang Terdaftar Di BEI Periode Tahun 2015-2019) - Utami, Agustina Surya; Ali, Karnila (Jurnal Manajemen DIVERSIFIKASI, 2021)
Abstract This research was conducted to assess the financial performance of companies engaged in the automotive sector listed on the Indonesia Stock Exchange, namely PT Astra Autoparts (AUTO), PT Selamat Sempurna Tbk (SMSM), PT Indospring Tbk (INDS), PT Garuda Metalindo Tbk (BOLT) and PT. Indo Kordsa Tbk (BRAM) research year period, which is five years from 2015 to 2019. The research approach used in this research is a quantitative approach. This research uses descriptive research. The subjects in this study are companies engaged in the automotive sector, especially companies that produce or sell spare parts listed on the Indonesia Stock Exchange for the period 2015-2019. The data analysis technique used is to calculate and analyze the company's financial statements using the Economic Value Added (EVA) method. The results of this study indicate that of the five companies studied, there was only one company that produced positive EVA values ​​during the five years of research, namely PT Selamat Sempurna Tbk (SMSM). Positive EVA means that the company is considered capable of providing added value for its shareholders. This research is expected to provide a reference and an overview of financial performance appraisal using the EVA method. Keywords: Financial Performance, Economic Value Added Method, EVA.